AC susceptibility and electrical properties of rare-earth- and alkali metal-substituted (Tl0.7M0.3)Sr2CaCu2O7 with M = Er, Gd, La, Na, K and Rb - Bakar, Ilhamsyah Putra Abu; Muhammad-Aizat, K.; Nur-Akasyah, J.; Mohd-Syahmi, M.S.; Mohd Suib, Nurul Raihan; Chiu, Wee Siong; Abd-Shukor, Roslan (Springer, 2019)
The effects of rare-earth elements M = Er, Gd and La, and alkali metals M = Na, K and Rb substitution on (Tl0.7M0.3)Sr2CaCu2O7 (Tl-1212) are reported. The rare-earth elements were chosen by considering the ionic radius, i.e., from the smallest (Er+3) to the largest (La+3) ion. The samples were prepared via the solid-state reaction method. X-ray diffraction patterns showed the presence of major Tl-1212 and minor Tl-1201 and Ca0.3Sr0.7CuO2 phase in almost all samples. The resistance versus temperature curves for the rare-earth-substituted samples showed onset temperature between 87 and 90 K and zero resistance temperature between 69 and 81 K. Alkali metal substitutions exhibited Tl-1212 phase but showed no superconducting transition although the electrical resistivity was much lower than the rare-earth-substituted samples. AC susceptibility measurement showed superconducting transition Tcχ, between 59 and 80 K for the rare-earth element-substituted samples. The average grain size, the transition temperature, Tcχ and the peak temperature Tp of the imaginary part of the susceptibility χ″ decreased as the ionic radius of the rare earths was reduced.